How does patient-centred communication reduce chronic disease risk in adults? exploring the sequential mediation of personal electronic health records and health literacy - Li, Jinran; Yingxia Zhu; Tan, Liuchang (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate the mediating roles of personal electronic health record usage and health literacy in the relationship between patient-centred communication and chronic diseases. Method: The study was conducted at Chongqing, China from September 2024 to December 2024, and used secondary data from the Health Information National Trends Survey related to adults aged 18 and above. Guided by the conceptual framework from patient-centred communication pathway models, the sequential mediating roles of behavioural and cognitive factors in the relationship between PCC and chronic disease were examined. Data was analysed using SPSS 27. Results: A negative association was found between the individual’s patient-centred communication scale and chronic diseases (p<0.001). Furthermore, patient-centred communication was negatively associated with chronic diseases through the serial mediation of personal electronic health record usage and health literacy (bp=-0.001, 95% confidence interval: -0.002–0.0004). Conclusion: Both personal electronic health record usage and health literacy sequentially mediated the relationship between patient-centred communication and chronic disease, highlighting the importance of these factors in enhancing health outcomes. Key Words: Patient-centred communication, Electronic health record use, Health literacy, Chronic disease.